Pola Manajemen Fudraising Wakaf Uang (Studi Kasus Pada Yatim Mandiri Cabang Kudus) - Eni Pratiwi, Jaenal Arifin, M. Nurul Qomar (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2020)
This study is concerned with zakat management organizations, infaq, alms and waqf, where there are fundraising activities, especially waqf. Fundraising is an activity in order to raise funds and other resources from the community, both individuals, organizations and legal entities. Fundraising requires good management. Management functions ranging from planning, organizing, actuating and controlling are implemented so that waqf fundraising runs well. With the existence of the Yatim Mandiri Kudus branch which is active in fundraising, it is hoped that it can maximize the potential of waqf in Kudus so that it can help people in need in Kudus, especially the dhu'afa orphans. The problem in this research is how to manage waqf fundraising at the Yatim Mandiri Kudus branch. This type of research is a descriptive field research with a qualitative approach. The data collection techniques use literature review, observation and in-depth interviews with the manager of the Yatim Mandiri branch of Kudus as primary and secondary data. The results of this study are the management of waqf fundraising at the Yatim Institute. Mandiri Kudus, it can be concluded that, Yatim Mandiri Kudus Planning is doing well, by making a program arrangement to be delivered, and by applying two fundraising methods, namely direct and indirect Fundraising. Organizing and directing have been carried out well, determining the area for taking, recruiting and mentoring new fundraisers, led directly by the head of the Yatim Mandiri Kudus branch. And also well-managed supervision, starting from measuring the performance of fundraiser employees and ongoing achievements. Meanwhile, the Kudus branch of the LAZNAS Yatim Mandiri institution itself has programs related to waqf and other programs, such as zakat, shadaqah, donation to support the institution.